A Bit Flipping Viterbi Decoding Algorithm Based on CRC Check for Convolutional Code - Sun, Yaping; Dou, Gaoqi; Yin, Hang (Proceedings (International Conference on Communication Technology. Online), 2021)
Soft output Viterbi decoding (SOVA) algorithm, as maximum likelihood decoding, is a convolutional code decoding algorithm commonly used in communication systems. In order to further improve the decoding performance and reduce the bit error rate, a bit flipping Viterbi decoding algorithm based on cyclic redundancy check (CRC) is proposed in this paper. In this paper, the concept of bit credibility is introduced, where CRC check is carried out after soft decision Viterbi decoding, and the credibility of bit information is utilized to flip the wrong bits, so as to improve the performance of frame error rate (FER). Simulation results show that the performance of the proposed algorithm is better than the SOVA algorithm and the SOVA algorithm based on CRC check with certain error-correcting ability.